1995
DOI: 10.1099/0022-1317-76-6-1521
|View full text |Cite
|
Sign up to set email alerts
|

Genetic stability of cold-adapted A/Leningrad/134/47/57 (H2N2) influenza virus: sequence analysis of live cold-adapted reassortant vaccine strains before and after replication in children

Abstract: We previously reported that the A/Leningrad/134/47/57 (H2N2) cold-adapted virus (A/Len/47) used in preparing reassortant live attenuated vaccines for children acquired 14 (11 coding) mutations in genes coding for proteins other than haemagglutinin and neuraminidase during cold-adaptation. Preservation of these mutations in genomes of viruses isolated from children on the second, fifth, or eighth day after vaccination was examined by sequence analysis. The sequence data demonstrated that all nine coding mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Indeed, these viruses will be restricted in their replication outside the upper respiratory tract. The ca/ts/att phenotype results from multiple mutations, and loss of attenuation would require reversion of multiple mutations, which is unlikely to occur in vivo [9] or in vitro. Indeed, we have demonstrated that these mutations are conserved after 15 successive passages of both master donor viruses (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these viruses will be restricted in their replication outside the upper respiratory tract. The ca/ts/att phenotype results from multiple mutations, and loss of attenuation would require reversion of multiple mutations, which is unlikely to occur in vivo [9] or in vitro. Indeed, we have demonstrated that these mutations are conserved after 15 successive passages of both master donor viruses (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, a trivalent live attenuated influenza vaccine (FluMist) containing two type A viruses (H1N1 and H3N2) and a type B virus has been licensed for use in humans since 2003 (2,3). Moreover, human LAIVs have been used for many years in Russia without the emergence of new influenza virus reassortants, thus demonstrating the stability of these attenuating phenotypes (2,3,14,38,46). In veterinary medicine, an equine influenza virus LAIV (Flu Avert I.N.…”
mentioning
confidence: 99%
“…The sequence analysis strategy used here to find unique residues in influenza type B sequences important for ts and att should be helpful to find yet-unknown att/ts residues in other attenuated viruses, such as ca A/Leningrad/134/57 or B/USSR/69 (16,17,27). It is noteworthy that the two wt residues (NP P410 and M1 H159) are conserved within both wt influenza type A and B viruses.…”
Section: Discussionmentioning
confidence: 99%